(untitled) (Journal of the College of Basic Education, 2022)
The State of China is moving rapidly towards gaining a privileged position in the world of economics and politics with the aim of strengthening its position and international strength and working to restore balance to the international system after it was lacking after the collapse of the former Soviet Union, and China’s economy is the second largest in the world after the economy of the United States of America. The gross domestic product amounted to 4.91 trillion US dollars, as its influence began to expand in all regions and countries of the world, including the African continent, which is related to the study, as the Chinese economic upgrading contributed to pushing it to go outside its national borders in search of raw materials from minerals, especially energy sources in general and oil Specially .